Penguatan Kewirausahaan Sosial dalam Pelaku UMKM: Integrasi Teknik Sipil dan Konseling untuk Pengelolaan Sumber Daya Alam - Ardiansyah Japlani; Eva Rolia; Eva Faliyanti; Hadi Pranoto; Dharmawan Dharmawan; Andiana Rosid; Jessica Norenza; Aulia Pangestu (SINAR SANG SURYA, 2025)
This community service program aimed to enhance the capacity of Small and Medium Enterprise (SME) actors in Kelurahan Iringmulyo, focusing on the development of social entrepreneurship based on natural resource management and clean water management. The program combined interdisciplinary expertise in social entrepreneurship, civil engineering (water management), and counseling to provide a holistic approach to capacity building. The activities included training on social entrepreneurship, practical techniques for sustainable water management, and counseling sessions aimed at improving teamwork and entrepreneurial motivation. A total of 15 participants from the local SME community were involved in the program. Pre- and post-test evaluations showed a significant increase in participants' understanding of social entrepreneurship and water management, with an average improvement of 35% and 40%, respectively. The counseling sessions also had a positive impact on the participants’ teamwork and motivation, with 85% of participants reporting increased confidence and a better understanding of the importance of collaboration in managing social enterprises. The program demonstrated positive results in empowering the participants by enhancing their entrepreneurial skills and providing them with the tools to manage natural resources efficiently. The ongoing mentoring and collaboration with external partners will ensure the sustainability of the knowledge and skills acquired during the program, contributing to the long-term development of the community. Overall, this initiative successfully equipped the SME actors with the necessary knowledge and motivation to manage socially impactful businesses and address local environmental challenges.